Strengthening Character Through Comparative Rhetoric and Istifham: A Study on E. Abdurrahman’s Thoughts on Character Education - Roni Nugraha; Joyce Bulan Basrawi; Adudin Adudin Alijaya (Khazanah Pendidikan Islam, 2024)
This article examines the Strengthening of Character through Comparative Rhetoric and Istifham (Rhetorical Questions): A Study of E. Abdurrahman’s Thoughts on Moral Education. As a second-generation activist of the PERSIS organization, besides being proficient in the field of fiqh, E. Abdurrahman demonstrated significant attention to moral education. He published at least 87 articles on moral education in various Islamic magazines between 1936 and 1983. The findings of this study indicate three key principles of moral education: moral education should be elevated from mere ability (bisa) to habitual practice (biasa); it must culminate in loyalty to God; and it should be student-centered, grounded in the philosophy of ngajeujeuhkeun. The concepts of "giving and sustaining life," "ensuring and promoting safety," and "establishing and maintaining security" are three essential terms used to define the goals of moral education. From the 87 articles, E. Abdurrahman’s core materials on moral education can be categorized into eleven topics: the purpose of life, the profile of the ideal human, the urgency of moral education, heart cultivation, life resources, justice, balance, the inner dimension of worship, food and drink, death, and shame. From the perspective of strengthening moral education, Abdurrahman positioned tawahum (empathy) as a pillar for determining the methods of moral education. At the implementation level, tawahum is associated with the teacher's ability to engage in persuasive communication by employing various rhetorical styles that touch emotions, such as comparative rhetoric and istifham.